Analysis of Cross-Sectional Capacity of the Jambi River in the Muaro Jambi Temple About Various Times of Flooding Using HEC-RAS Software - Mayasari, Putri; Ilfan, Freddy; Yasdi, Yasdi; Rimba, Rimba (Civil and Environmental Science Journal (CIVENSE), 2021)
Jambi River is one of the rivers located in the Muaro Jambi Temple Complex Area, Muaro Jambi Regency, Jambi Province. Muaro Jambi Temple is one of the tourist attractions in Jambi Province. This study aims to find the capacity of Jambi River tested by planned flood discharge utilizing (synthetic unit hydrograph) HSS Nakayasu method for a return period of two, five, ten, twenty-five, fifty and hundred years. HEC-RAS software used to analyse the water level in the Jambi River towards the flood potential that causes the submerging of the Kedaton Temple building. This research used the log Pearson type III method to calculate the planned rain return period and used the Nakayasu synthetic unit method to calculate the planned flood discharge. The analysis showed that the Jambi River could not load the flood discharge in the five, ten, twenty-five, fifty, and one hundred years return period at several measurement points: river sta-1, river sta-2 and river sta-5. The floodwater level did not cause the Kedaton Temple building to be flooded from the simulation result.